p63 mediates an apoptotic response to pharmacological and disease-related ER stress in the developing epidermis - Pyati, Ujwal J. (2011)
Endoplasmic reticulum (ER) stress triggers tissue-specific responses that culminate in either cellular adaptation or apoptosis, but the genetic networks distinguishing these responses are not well understood. Here we demonstrate that ER stress induced in the developing zebrafish causes rapid apoptosis in the brain, spinal cord, tail epidermis, lens and epiphysis. Focusing on the tail epidermis, we uncover an apoptotic response that depends on Puma, but not on p53 or Chop. Puma is transcriptionally activated during this ER stress response in a p53-independent manner, and is an essential mediator of epidermal apoptosis. We demonstrate that the p63 transcription factor is upregulated to initiate this apoptotic pathway and directly activates puma transcription in response to ER stress. We also show that a mutation of human Connexin 31, which causes erythrokeratoderma variabilis, induces ER stress and p63-dependent epidermal apoptosis in the zebrafish embryo, thus implicating this pathway in the pathogenesis of inherited disease.